The Effect of Ascending and Descending Fartlek Training on the Development of Specific Speed for 3000 Meter Runners According to Target Time for Track and Field Youth Athletes - طنيبة, ساعد; سعودي, سليم (Journal of Sport Science Technology and Physical Activities, 2025)
The objective of the study aims to identify the effect of ascending and descending fartlek training methods on the special speed of 3000-meter runners under 18 years old. For this purpose, we used the experimental method on a sample composed of 12 athletes, chosen purposively from track and field runners in Jijel. For data collection, we used physical fitness tests. After collecting the results and having treated them statistically using the SPSS statistical package, we concluded that both ascending and descending fartlek training methods positively affected the special speed of the runners, with significant statistical differences observed in favor of the experimental groups. On this basis, the study recommended the application of ascending fartlek training as an effective method for improving special speed in 3000-meter runners under 18 years old